Prostate Cancer Screening Decisions: Which Aspects Do Men Value Most? An Interview Study With Men Invited to a Population-Based Program - Linda Svensson; Ola Bratt; Jonas Hugosson; Karin Stinesen (American Journal of Men's Health)
This study explores aspects that men consider when deciding whether to participate in a prostate cancer screening program and how the information in the invitation letter contributed to their decision. Semi-structured interviews were conducted with 50- to 62-year-old men invited by letter to a population-based prostate cancer screening program. Data from transcribed interviews were analyzed using qualitative content analysis using manifest and indicative approaches. Eighteen men were interviewed, 10 whom chose to be tested, and 8 who declined screening. The information in the invitation letter was not decisive for whether men chose to be tested or not. The aspects that the men valued in their personal decision to participate or refrain from screening were categorized as (a) the expectation that authorities should take responsibility and provide guidance; (b) fear, which was described as both a driving force and a barrier; (c) reliance upon intuition combined with seeking social and emotional support; (d) the perception of one’s own risk of being affected. Men who relied on risk assessment mentioned difficulties in evaluating the information about the potential disadvantages of screening. Our findings suggest that the intention of informed decision-making for prostate cancer screening is difficult to fully realize. Further research is needed to understand how the individual decision-making process is influenced by factors such as assessment of personal risk, perception of advantages and disadvantages, and cultural background, and to optimize the information to the invited men.